2020
DOI: 10.3390/ijerph17124528
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Barriers and Opportunities for Effective Management of Shared Sanitation in Low-Income Settlements—The Case of Kumasi, Ghana

Abstract: Improved sanitation for all is a daunting task for low-income countries, and shared toilets often provide an alternative to private household sanitation for most urban residents. This study sought to provide better understanding of the existing barriers and opportunities for improved management of shared sanitation. The study used focus group discussions and in-depth interviews with 70 users (landlords and tenants) of shared sanitation in Kumasi, Ghana to assess barriers and opportunities of “high-quality” sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 38 publications
2
16
2
Order By: Relevance
“…An additional two FGDs were then held with landlords and tenants as participants in the same group to verify that all information from the previous discussions had been captured. The interview and group discussion guides developed for this study have been published elsewhere [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…An additional two FGDs were then held with landlords and tenants as participants in the same group to verify that all information from the previous discussions had been captured. The interview and group discussion guides developed for this study have been published elsewhere [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…In many of the prior studies conducted in Ethiopia and other African nations having a larger family, an advanced education, and being male were associated with the increased adoption and utilization of latrines [16][17][18][19]. Also, Qualitative studies on sanitation have identified the un-affordability of building materials [20] and the lack of awareness of the health risks associated with open defecation as a hindrance to the adoption of sanitation facilities [21]. Nevertheless, the majority of the studies focused on a single-level analysis [22][23][24].…”
Section: Fundingmentioning
confidence: 99%
“…Similarly, the most common type of toilet facilities was shared pit latrine with a slab (67%) with no hand-washing facilities in Kampala, Uganda ( Ssemugabo et al, 2020 ). In Ghana, 40% of commonly used toilet facilities were dry toilets (pit latrines), and between 2 and 21 households, or 4 and 84 people shared one facility, ( Antwi-Agyei et al, 2020 ), and more than 25% of households engaged in open defecation ( Adzawla et al, 2020 ). In short, toilet facilities in low-income countries are critical and need to be improved.…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, it might increase the risk of COVID-19 transmission. Given that plentiful households shared toilet facilities (most of them were pit latrines) with poor ancillary facilities (such as hand-washing facilities) were common in low-income countries ( Antwi-Agyei et al, 2020 ; Ssemugabo et al, 2020 ), we believed that the use of pit latrines in rural China and low-income countries would increase the contact between human, thus increasing the risk of COVID-19 transmission to a certain extent.
Fig.
…”
Section: Resultsmentioning
confidence: 99%